The platelet indices in pediatric patients with acute appendicitis - Yılmaz, Yunus; Kara, Fatih; Gümüşdere, Musa; Arslan, Hasan; Üstebay, Sefer (International Journal of Research in Medical Sciences, 2017)
Background: The diagnosis of Acute Appendicitis (AA) remains a problem in pediatric population. It has been suggested that Mean Platelet Volume (MPV) is lower in the patients with AA. The purpose of this study was to investigate the diagnostic value of platelet indices in pediatric AA cases. Methods: A retrospective case-controlled study was designed: 224 subjects were included in this study. All patients had been operated on in division of pediatric surgery at the Kars Government Hospital with the preliminary diagnosis of AA. 204 and 20 of these patients were pathologically diagnosed as AA (group 1) and normal appendix vermiformis (group 2), respectively. Platelet indices had been studied in the biochemistry laboratory of the hospital, before the surgery. Results: In group 1, platelet count, mean platelet volume, plateletcrit and platelet distribution width were 305 ± 94x103/µL; 7.37 ± 0.90 fL; 0,220 ± 0.057 % and 16.3 ± 0.5%, respectively. In group 2, platelet count, mean platelet volume, plateletcrit and platelet distribution width were 283 ± 85 103/µL; 7.60 ± 1.24 fL; 0.208 ± 0.045 % and 16.4 ± 0.7%, respectively. There was no statistically significant difference between the groups studied with regard to platelet indices (P>0.05). Conclusions: Our study showed that platelet indices have no diagnostic value in the diagnosis of AA at pediatric age group.